Food skills confidence and household gatekeepers' dietary practices. (1st January 2017) - Burton, Melissa; Reid, Mike; Worsley, Anthony; Mavondo, Felix
Abstract: Introduction: Household food gatekeepers have the potential to influence the food attitudes and behaviours of family members, as they are mainly responsible for food-related tasks in the home. The aim of this study was to determine the role of gatekeepers' confidence in food-related skills and nutrition knowledge on food practices in the home. Methods: An online survey was completed by 1059 Australian dietary gatekeepers selected from the Global Market Insite (GMI) research database. Participants responded to questions about food acquisition and preparation behaviours, the home eating environment, perceptions and attitudes towards food, and demographics. Two-step cluster analysis was used to identify groups based on confidence regarding food skills and nutrition knowledge. Chi-square tests and one-way ANOVAs were used to compare the groups on the dependent variables. Results: Three groups were identified: low confidence, moderate confidence and high confidence. Gatekeepers in the highest confidence group were significantly more likely to report lower body mass index (BMI), and indicate higher importance of fresh food products, vegetable prominence in meals, product information use, meal planning, perceived behavioural control and overall diet satisfaction. Gatekeepers in the lowest confidence group were significantly more likely to indicate more perceived barriers to healthy eating, report more time constraints and more impulse purchasing practices, and higher convenience ingredient use. Other smaller associations were also found. Conclusion: Household food gatekeepers with high food skills confidence were more likely to engage in several healthy food practices, while those with low food skills confidence were more likely to engage in unhealthy food practices. Food education strategies aimed at building food-skills and nutrition knowledge will enable current and future gatekeepers to make healthier food decisions for themselves and for their families.